1976
DOI: 10.1007/bf00011146
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization and gaseous losses of nitrogen from urea and ammonium sulphate in salt-affected soils

Abstract: An incubation study on mineralization and gaseous losses of nitrogen was conducted on three soils with increasing levels (1.1 to 50 mmhos/cm) of salinity and two levels of urea and ammonium sulphate upto 6 weeks. Mineralization of nitrogen increased with time and decreased with the increase of salinity. It was more from ammonium sulphate than urea, and relatively more from the lower dose. The gaseous losses of NH4-N increased with salinity. About 35 ~ 5 per cent of added N was lost in the gaseous form at maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…However, the reported leakiness of roots under saline conditions (Meharg and Killham 1991;Vieira-Santos et al 2001) and the role of cellular material thus released in affecting rhizospheric microbial functions will have a significant influence on the plant growth and productivity. Form and availability of N further add to these effects since nitrification is retarded under saline conditions (Gandhi and Paliwal 1976;Westerman and Tucker 1974), leaving the plants with NH 4 + as the predominant source of N. In the present study, rooting medium salinity had in general a growth retarding effect (Fig. 2).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the reported leakiness of roots under saline conditions (Meharg and Killham 1991;Vieira-Santos et al 2001) and the role of cellular material thus released in affecting rhizospheric microbial functions will have a significant influence on the plant growth and productivity. Form and availability of N further add to these effects since nitrification is retarded under saline conditions (Gandhi and Paliwal 1976;Westerman and Tucker 1974), leaving the plants with NH 4 + as the predominant source of N. In the present study, rooting medium salinity had in general a growth retarding effect (Fig. 2).…”
Section: Discussionmentioning
confidence: 70%
“…The inhibitory effects of NH 4 are more severe for plants grown under saline conditions (Lewis et al 1989;Khan et al 1994). Incidentally, however, NH 4 + should generally be considered as the predominant form of N in saline soils due to inhibition of nitrification (Westerman and Tucker 1974;Gandhi and Paliwal 1976). Therefore, plant species capable of growing under saline conditions may have evolved both morphological and physiological adaptations for uptake and assimilation of NH 4 + (Martins-Loução et al 2000).…”
Section: Introductionmentioning
confidence: 97%
“…This helps to reduce the ammonium concentration of soil solution, a soil has high CEC, there will be minimum chances of NH3 volatilization and vice versa (Whitehead and Raistrick, 1993). Soil salinity: With many other factors, high level of soil salinity is also an important factor involved in ammonia volatilization (Gandhi and Paliwal, 1976;McClung and Frankenberger. 1985).…”
Section: Factors Affecting Ammonia Volatilizationmentioning
confidence: 99%
“…However, the losses increased with the increase in salinity. Gandhi and Paliwal (2004) measured about 35 ± 5% gaseous N losses at a maximum salinity value (ECe = 45 to 50 mmhos cm -1 ). They also observed that salinity and pH both correlated negatively with the N mineralization and positively with the gaseous losses of ammonia.…”
Section: Introductionmentioning
confidence: 99%